2005
DOI: 10.1016/j.femsle.2005.04.017
|View full text |Cite
|
Sign up to set email alerts
|

The stabilization of housekeeping transcripts inTrypanosoma cruziepimastigotes evidences a global regulation of RNA decay during stationary phase

Abstract: The relative steady state concentration of mRNAs of four housekeeping single-copy type Trypanosoma cruzi genes (actin, triosephosphate isomerase, trypanothion reductase and the ribosomal protein S4) was analyzed throughout the growth curve. A distinguishable pattern was observed with maximal levels occurring at the logarithmic phase of growth and minimum levels occurring at the stationary phase. The half-lives of all analyzed messenger RNAs, and also of three molecular species of immature ribosomal RNAs were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Up to now, general and conserved mechanisms controlling gene expression in trypanosomes undergoing environmental stresses have eluded detection. It has been proposed that T. cruzi epimastigotes growing logarithmically have higher mRNA degradation rates than parasites in the stationary phase of growth (Cevallos et al ., 2005), where parasites have decreased transcription (Elias et al ., 2001). Also, RNA synthesis is known to be repressed in stationary‐phase T. brucei parasites (Pays et al ., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, general and conserved mechanisms controlling gene expression in trypanosomes undergoing environmental stresses have eluded detection. It has been proposed that T. cruzi epimastigotes growing logarithmically have higher mRNA degradation rates than parasites in the stationary phase of growth (Cevallos et al ., 2005), where parasites have decreased transcription (Elias et al ., 2001). Also, RNA synthesis is known to be repressed in stationary‐phase T. brucei parasites (Pays et al ., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…When total transcription activity was compared between actively growing epimastigotes and cultures at the stationary phase, it was found that epimastigotes from the exponential phase are about six-to to tenfold more active in transcription than stationary cells (Nepomuceno-Mejia et al 2010). In such a scenario, the steady-state abundance of individual housekeeping mRNAs such as actin, triosephosphate isomerase, trypanothion reductase, and the ribosomal protein S4 is reduced to less than half throughout the stationary phase (Cevallos et al 2005). Quite interestingly, the half-life of these transcripts (and of precursor rRNA species) is expanded by three-to sevenfold in these stationary cultures.…”
Section: Transcriptional and Posttranscriptional Eventsmentioning
confidence: 99%
“…Agreeing with these findings, an expanded mRNA half-life could be shown in EMFs of T . cruzi [ 49 ]. By global down regulation of RNA decay in non-dividing EMFs, housekeeping transcripts could be stabilized to ensure basic functions a life cycle stage of generally repressed metabolism [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Transcripts in EMFs have exceptionally long half-lives in T . cruzi [ 49 ], emphasizing the relevance of post-transcriptional gene regulation to limit the amount of protein translated from the stable mRNA stock. This concept of minimizing cell metabolism is considered to secure a pool of long living, non-dividing EMFs in the tsetse fly, which can return to proliferation when nutrition is provided [ 49 ].…”
Section: Resultsmentioning
confidence: 99%